Cultural Evolutionary Theory and the Significance of the Biology-Culture Analogy. Issue 2 (March 2021) - Stanley, Shaun
Throughout the literature on Cultural Evolutionary Theory (CET) attention is drawn to the existence and significance of an analogy between biological phenomena and socio-cultural phenomena (the "biology-culture analogy"). Mesoudi (2017) seems to argue that it is the accuracy of the analogy, and the magnitude of accurate instances of this analogy at work, which provides warrant for an evolutionary approach to the study of socio-cultural phenomena, and, thus, for CET. An implication of this is that if there is evidence to suggest that the analogy is not accurate, or that there aren't many cases where it is accurate, this would constitute evidence to reject an evolutionary approach to the study of socio-cultural phenomena. As such, opponents of CET raise objections highlighting the weakness of the biology-culture analogy. These objections, in turn, have standard replies in the literature that serve to reinforce the realism of the biology-culture analogy. Curiously, this situation would appear to support a position in the philosophy of social science called "Ontology Matters" (Lauer 2019). It is the view that social ontology can contribute to the empirical success of the social sciences (among which I include CET) by providing an accurate account of what there is in the domain of the social world which can be used to generate better explanations and/or predictions of social phenomena. If ontology matters, in this sense, perhaps this can help to clarify and resolve the dispute regarding the realism of the biology-culture analogy. In turn, perhaps this can help us determine what warrant there is for CET. However, I think this situation is indicative of severe confusion and misunderstanding as to the significance of the biology-culture analogy. This confusion is caused by inattention to two things. First, the useful distinction between it's methodological, epistemological, and ontological significance. Second, the abstract (ontologically minimalist) nature of Darwinian evolution by natural selection. By drawing attention to these two things, I hope to take the sting out of, and deflate the significance of, disputes regarding the accuracy of the analogy, for both proponents and opponents of CET, as well as to bring into contact a classical dispute in the philosophy of social science with some relevant aspects of theoretical biology.